PERANCANGAN APLIKASI AKUNTANSI PABRIK BERBASIS WEBSITE - Fritz Gamaliel; P.Yudi Dwi Arliyant (Jurnal Manajamen Informatika Jayakarta, 2021)
The financial information that has been made by the accountant can now be easily accessed by the part of the leadership. However there are difficulties faced by the leaders as well as accountants, one that is non-uniformity of financial document format. This has resulted in the related division must input the financial document data which is the task of their division into the system. After that, the division sends the documents to the accountant for then the accountant enters it back into the system. This causes work to be inefficient because it has to be entered twice. In this research, the application was made with the concept of uniform financial document formats so that one entry is sufficient. Application is made using the PHP programming language and MySQL database. The existence of the study expected that Application can improve the quality of financial reporting in the process recording the financial report